Ambipolar transistors based on random networks of WS2 nanotubes. (9th June 2016) - Sugahara, Mitsunari; Kawai, Hideki; Yomogida, Yohei; Maniwa, Yutaka; Okada, Susumu; Yanagi, Kazuhiro
Abstract: WS2 nanotubes are rolled multiwalled nanotubes made of a layered material, tungsten disulfide. Their fibril structures enable the fabrication of random network films; however, these films are nonconducting, and thus have not been used for electronic applications. Here, we demonstrate that carrier injection into WS2 networks using an electrolyte gating approach could cause these networks to act as semiconducting channels. We clarify the Raman characteristics of WS2 nanotubes under electrolyte gating and confirm the feasibility of the injection of electrons and holes. We reveal ambipolar behaviors of the WS2 nanotube networks in field-effect transistor setups with electrolyte gating.